The analysis of the deformation of node in a modular scaffolding system - Pieńko, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The paper deals with the deformation of the weakest point of the modular scaffolding systems, which is the node. Scaffoldings are reusable constructions which can have various forms of the load, depending on the destination. The connections between the elements of scaffolding are not permanent and obvious. The multi-hole rosette allows to connect up to eight components, each of which can be loaded in another way. The proper design of scaffolding structures requires knowledge of the behavior of nodes under the load. Every kind of a one-piece load was analyzed in the study (normal force, cutting and bending moment), which will provide the basis for further studies with a larger number of elements. This paper presents original solutions that allow to load the node in the testing machine.